Virucidal effects of various agents—including protease—against koi herpesvirus and viral haemorrhagic septicaemia virus - Amtmann, Anette; Ahmed, Ibrahim Abdulla; Zahner-Rimmel, Petra; Mletzko, Adam; Jordan, Lisa; Oberle, Martin; Wedekind, Helmut; Christian, Jürgen; Bergmann, Sven Michael; Becker, Anna (Journal of Fish Diseases, 2019)
In a search for alternative, environmentally friendly and effective disinfecting agents, a commercially available protease—Neutrase®—was tested in this work for inactivation of koi herpesvirus (KHV) and of viral haemorrhagic septicaemia virus (VHSV). For comparison, the stability of these viral pathogens in similar configurations at various pH values and concentrations of peracetic acid or quicklime, typically used for disinfection, was tested. Therefore, virus suspensions were incubated with various concentrations of different agents for 24 hr and the titre of the remaining infectious particles was determined by virus titration. Furthermore, the treatment of both viruses, with the agents at concentrations that were previously appointed as effective, was also examined in the presence of solid material (quartz sand). All procedures investigated in this study, including the protease treatment, were able to reduce the titre of KHV and VHSV below the detection limit of the titration. Although further studies are necessary, this is the first report of the application of a protease for the inactivation of the selected fish pathogens, demonstrating the great potential of the latter for disinfection.
CRIS-Team Scopus Importer:2019-12-03
Keywords: disinfect; koi herpesvirus; proteases; viral haemorrhagic septicaemia virus